Determinants and modelling primary market spread of securitisation for entrepreneurs in Malaysia - Seng, Ngau Duo (2020)
Securitisation includes the transfer of illiquid resources to investors where such exchange is supported by the issuance of obligation securities called Asset-Backed Debt Securities (ABS) through a Special Purpose Vehicle (SPV). The under-utilisation of bonds or the absence of enhancement of the firm credit portfolio resulted in financial difficulties being faced by companies during the financial crisis in 1997. It was subsequently thought that securitisation might be an alternative source of funds that could enable companies to broaden the financial portfolios of their organisations. However, more information and knowledge of securitisation was needed in Asia, including in Malaysia. The fundamental focus in this investigation is on the determinants of primary market spread on RMBS, CMBS and ABS, and this study intends to inspect 12 years of information, from 2004 to 2016. Past examinations have left gaps in this area of research. The research objectives are the investigation of the determinants that incorporate domestic macroeconomic variables (GDP, Bursa Malaysia Kuala Lumpur Composite Index and political index) as determinants of the primary market spread and to examine whether additional variables of currency risk and Standard and Poor 500 can be included as determinants of the primary market spread and the impact on internal determinants when domestic macroeconomic factors are present in the primary market spread of securitisation in Malaysia. Lastly, develop and test the final models or framework consisting of determinants of primary market spread in Malaysia. The exploration adopts a quantitative technique in investigating the information gathered which is focus on pools Ordinary Least Square (OLS), fixed effect and random effect analysis. The corporate obligation pricing theory created by Merton (1974) and embraced by Vink (2008) was utilised in this study as the base for building up another model that would be suitable for Malaysia’s securitisation markets. Regarding the primary market spread in Malaysia, domestic macroeconomic factors such as gross domestic product, stock index and political index showed significance in the primary market spread in three of the control models, and originators may want to take this economic issue into consideration before issuing securitised products. In addition, global macroeconomic determinants such as currency risk and stock market index such as Standard and Poor 500 also play an important role in influencing the asset pricing, need to be cautious when the global economy is not doing well, especially in the United States. The fixed effect model for liquidity, tranches, maturity, gross domestic product and political index are the main factors of the primary market spread in Malaysia while random effect model, exhibit that debt to equity, currency risk, Standard and Poor 500, gross domestic product, stock market index and political risk are the main factors of primary market spread in all these models. The study concludes that domestic and global determinants play an important role in deciding the primary market spread of securitisation in Malaysia. Lastly, policy makers and entrepreneurs can also use this study results to target the timing and take in the consideration of domestic and global determinants when issuance securitisation.